2019
DOI: 10.1111/iwj.13023
|View full text |Cite
|
Sign up to set email alerts
|

Medical device‐related pressure ulcer (MDRPU) in acute care hospitals and its perceived importance and prevention performance by clinical nurses

Abstract: The incidence rate of patients developing pressure ulcers associated with medical device use is underreported in Korea. This study aims to determine clinical nurses' perceived importance and performance towards medical device‐related pressure injury prevention. A total of 620 nurses from seven hospitals attending continuing education programmes in Korea responded to self‐administered questionnaires. Data were collected from March to December 2017 on a 4‐point‐Likert scale on nurses' perceived importance and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 22 publications
5
42
0
4
Order By: Relevance
“…14 In addition to this assessment, it is essential that nurses prioritize the early identification of these injuries by means of regular skin inspections, at least once each shift, particularly in the case of patients with risk factors for the development of injuries, such as localized or systemic edema. 6,15 The professionals' understanding of the risk for the development of MDR PIs, present in DSC2, is in line with the literature. An Australian study identified that people hospitalized in the ICU are 3.8 times more likely to develop a pressure injury when compared to those hospitalized in the wards.…”
Section: Dsc5supporting
confidence: 59%
“…14 In addition to this assessment, it is essential that nurses prioritize the early identification of these injuries by means of regular skin inspections, at least once each shift, particularly in the case of patients with risk factors for the development of injuries, such as localized or systemic edema. 6,15 The professionals' understanding of the risk for the development of MDR PIs, present in DSC2, is in line with the literature. An Australian study identified that people hospitalized in the ICU are 3.8 times more likely to develop a pressure injury when compared to those hospitalized in the wards.…”
Section: Dsc5supporting
confidence: 59%
“…ese ndings are consistent with published data from other centres. 106 Categorisation Table 5 presents an example of categorisation of medical devices, based on how they interact with the skin and the aetiology of the subsequent DRPU. is method of categorising devices focuses the health professional on the reasons for the associated DRPU risk.…”
Section: Impact By Type Of Devicementioning
confidence: 99%
“…At present, health professionals and administrators are often not even aware of the importance of DRPU and its associated risks. 9,106 Similarly, chart templates and patient documentation may not pay much attention to DRPU prevention. 9 ere is a need, therefore, to raise awareness of DRPU through education, ongoing training and consistent reporting.…”
Section: Increasing Awarenessmentioning
confidence: 99%
“…According to Nuru et al (2015), having higher educational status, attending formal training and having nursing experience were positively associated with knowledge and practice regarding pressure injury prevention. In fact, research by Kim, Lee, and the Korean Association of Wound Ostomy Continence Nurses (2019) revealed that education based on clinical practice was effective in communicating the importance on MDRPI prevention. Moreover, regular feedback and reflection on the quality of care illuminated areas for improvement (Sving, Fredriksson, Gunningberg, & Mamhidir, 2017).…”
Section: Introductionmentioning
confidence: 99%